Establishment of a 13C-positional isotope labelling approach and comparative investigation of metabolic fluxes in mesophyll and guard cells - Reis, André Guilherme Daubermann (2020)
Guard cells respond to a wide range of stimuli in order to change its volume and, thus, open or close the stomatal pore. Several stimuli cause changes in guard cells turgor, such as light, CO2, phytohormones, among others. Guard cells metabolism have differences in comparison with mesophyll cells. For instance, whilst the metabolic flux throughout the tricarboxylic acid (TCA) cycle is inhibited by light in mesophyll cells, evidences suggest that guard cells TCA cycle is active in presence of light. In this sense, this work aimed to investigate the metabolic fluxes through the TCA cycle and other associated pathways, such as glycolysis and CO2 fixation mediated by phosphoenolpyruvate carboxylase (PEPc). For this purpose, we stablished a mass spectrometry-based 13C-positional isotope labelling approach to analyse previously published gas-chromatography coupled to mass spectrometry data. Several metabolites of, or associated to the TCA cycle were evaluated in terms of relative isotopomer abundance, total 13C-enrichment and metabolite content, and the results from guard cells were compared with mesophyll cells of C3 or C4 plants, as well as to source or sink C3-mesophyll cells. In this sense, the results suggest that guard cells have a particular metabolic flux mode throughout TCA cycle and associated pathways, with certain similarities with mesophyll cells of C3 plants. Furthermore, the results indicate that the light-dependent inhibition of pyruvate dehydrogenase severely restricts the fluxes of carbon to glutamate synthesis. Results are discussed in the context of TCA cycle regulation and guard cell metabolism.